2003
DOI: 10.1016/s0014-5793(03)01219-5
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of intracellular caged sphingosine‐1‐phosphate causes Ca2+ mobilization independently of G‐protein‐coupled receptors

Abstract: Sphingosine-1-phosphate (S1P), the product of sphingosine kinase, activates several widely expressed G-proteincoupled receptors (GPCR). S1P might also play a role as second messenger, but this hypothesis has been challenged by recent ¢ndings. Here we demonstrate that intracellular S1P can mobilize Ca 2+ in intact cells independently of S1P-GPCR. Within seconds, S1P generated by the photolysis of caged S1P raised the intracellular free Ca 2+ concentration in HEK-293, SKNMC and HepG2 cells, in which the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 39 publications
(56 reference statements)
3
82
0
Order By: Relevance
“…It is concluded that the cis-4M-S1P that was produced by SphK1 mobilized Ca A c c e p t e d M a n u s c r i p t 14 the stores as previously demonstrated for S1P [12], and that relatively high concentrations of cis-4M-Sph are required for this effect. However, another mechanism, for example activation not of S1P receptors or G i -coupled receptors but other plasma membrane receptors, cannot be fully excluded.…”
Section: Page 37 Of 54supporting
confidence: 59%
See 3 more Smart Citations
“…It is concluded that the cis-4M-S1P that was produced by SphK1 mobilized Ca A c c e p t e d M a n u s c r i p t 14 the stores as previously demonstrated for S1P [12], and that relatively high concentrations of cis-4M-Sph are required for this effect. However, another mechanism, for example activation not of S1P receptors or G i -coupled receptors but other plasma membrane receptors, cannot be fully excluded.…”
Section: Page 37 Of 54supporting
confidence: 59%
“…Finally we wondered whether acute [Ca 2+ ] i increases by cis-4M-Sph were due to activation of G-protein-coupled S1P receptors. Although it is well known that S1P-induced [Ca 2+ ] i increases in HEK-293 cells are fully blocked by PTX and thus mediated by G i -coupled receptors [12], [Ca 2+ ] i increases by cis-4M-Sph were not at all affected by PTX (Fig. 3E) and thus not mediated by G-protein-coupled S1P receptors in these cells.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…So far, most evidence in the literature supports S1P receptor-mediated activation of the PI3K/PKB cascade. However, intracellular S1P can activate signal transduction and acutely triggers intracellular Ca 2q mobilisation (Meyer zu Heringdorf et al, 2003) and stimulates cell proliferation of fibroblasts (van Brocklyn et al, 1998).…”
Section: Discussionmentioning
confidence: 99%